(R)evolution interrupted? A collective reflection on equality and anti-discrimination law in a climate of regression - Štajnpihler Božič, Tilen (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2025)
The article reassesses the trajectory of European anti-discrimination law from the "revolution" of 2000 - marked by the EU Racial Equality and Employment Equality Directives - to the more sobering climate surrounding their 25th anniversary in 2025. While the Directives broadened protection and introduced potent enforcement tools (including burden-of-proof rules and requirements for effective sanctions), the momentum of EU equality law has largely stalled. The clearest symbol is the Horizontal Directive proposal, blocked in the Council since 2008, alongside only modest and often consolidating developments in EU secondary law, mostly in the gender field. The author, therefore, asks how anti-discrimination law can be advanced in a political and social landscape increasingly different from the one that enabled the 2000–2004 expansion. Drawing on collective reflection at the 12th Annual Berkeley Center on Comparative Equality and Anti-Discrimination Law Conference in Ljubljana (2025), the author distils three interlinked themes. First, he maps contemporary challenges: entrenched discriminatory attitudes, institutional bias, weak enforcement marked by political and judicial obstacles, data deficits, and the practical difficulty of addressing intersectional and algorithmic discrimination. Second, he outlines possible responses that build on a dual strategy of defence and adaptation: the principle of non-regression o human rights standards as a shield against rollback, alongside equality mainstreaming, strategic litigation, and complementary policy tools that may bypass legislative dead-lock. Third, he highlights the importance of inspiration as a professional and civic resource, emphasising professional responsibility, coalition-building beyond the juridical field, and persistence amid setbacks.
Keywords: človekove pravice; enakost spolov; pravo enakosti; pravo varstva pred diskriminacijo; protidiskriminacijsko pravo EU; raznolikost; vključenost